2013
DOI: 10.1111/jnc.12628
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of hydralazine in rat spinal cord injury‐attenuation of acrolein‐mediated damage

Abstract: Acrolein, an α,β-unsaturated aldehyde and a reactive product of lipid peroxidation, has been suggested as a key factor in neural post-traumatic secondary injury in SCI, mainly based on in vitro and ex vivo evidence. Here we demonstrate an increase of acrolein up to 300%; the elevation lasted at least two weeks in a rat SCI model. More importantly, hydralazine, a known acrolein scavenger can provide neuroprotection when applied systemically. Besides effectively reducing acrolein, hydralazine treatment also resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 65 publications
4
87
0
Order By: Relevance
“…Binding of acrolein to hydralazine is initiated through a Michael addition reaction between the carbonyl and hydrazine functional groups, respectively [97]. Hydralazine application has demonstrated significant benefit by exhibiting therapeutic concentrations in CNS only 2 hours after application [63]. Specifically, 20 μmol/L of hydralazine was detected in spinal cord tissue 2 hours following an intraperitoneal (IP) injection, which is comparable with a previous established therapeutic concentration [98].…”
Section: Mitigating Acrolein-mediated Myelin Damage and Improving Funmentioning
confidence: 85%
See 1 more Smart Citation
“…Binding of acrolein to hydralazine is initiated through a Michael addition reaction between the carbonyl and hydrazine functional groups, respectively [97]. Hydralazine application has demonstrated significant benefit by exhibiting therapeutic concentrations in CNS only 2 hours after application [63]. Specifically, 20 μmol/L of hydralazine was detected in spinal cord tissue 2 hours following an intraperitoneal (IP) injection, which is comparable with a previous established therapeutic concentration [98].…”
Section: Mitigating Acrolein-mediated Myelin Damage and Improving Funmentioning
confidence: 85%
“…The presence of acrolein has been implicated in cases of enhanced oxidative stress, particularly where elevated tissue and systemic levels of acrolein have been shown in both SCI [55, 56, 6164] and MS [57]. In fact, acrolein can increase up to 300% at 24 hours post-SCI and remain elevated for at least two weeks in a clinically relevant rat spinal cord contusion injury model [63]. Given that demyelination is a hallmark of both MS and SCI, this evidence points toward acrolein-mediated myelin damage as a key factor underlying symptoms of CNS trauma and disease.…”
Section: Acrolein-mediated Myelin Damagementioning
confidence: 99%
“…Studies have been conducted to mitigate acrolein mediated oxidative damage and neuronal injury by use of acrolein scavengers, most notably hydralazine (59). Park et al showed that daily intraperitoneal injections of hydralazine were effective in reducing acrolein levels, motor deficits and neuropathic pain in contusive SCI model (60). Hydralazine has a half-life period of a few hours (61) and this can be a limiting factor for experimental and clinical studies.…”
Section: Drugs and Drug Delivery Systemsmentioning
confidence: 99%
“…In this study, we used an acrolein scavenger, hydralazine, which is known to neutralize free acrolein [78,79] and acrolein-protein adducts [47,80], both of which are cytotoxic. Also, hydralazine was shown to effectively prevent acrolein-mediated cell death and tissue damage in spinal cord injury [46,81]. Additionally, we also used carnosine (beta-alanyl histidine, an endogenous dipeptide) that is known to scavenge aldehydes such as acrolein, and to have beneficial effects against acetaminophen-induced liver injury [82].…”
Section: Acrolein Scavengers Exhibited Protective Effects Both In Vitmentioning
confidence: 99%
“…Hydralazine (5mg/kg body weight, dose based on previous literature [79,81]) was administered by daily intraperitoneal injection during the 10-day alcohol feeding regimen. As noted previously, consumption of the alcohol diet resulted in significant hepatic acrolein adduct accumulation and steatosis in the liver, and the acrolein scavenger hydralazine effectively blocked alcohol-induced acrolein formation and adduct accumulation ( Figure 14B) and dramatically reduced hepatic steatosis as seen by histological examination and confirmed by Oil Red O staining ( Figure 14B).…”
Section: Acrolein Scavengers Exhibited Protective Effects Both In Vitmentioning
confidence: 99%